2012
DOI: 10.1016/j.ceca.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient restriction preserves calcium cycling and mitochondrial function in cardiac myocytes during ischemia and reperfusion

Abstract: Nutrient restriction (NR) prolongs longevity via enhanced mitochondrial function. To test the hypothesis that NR enhances resistance to ischemia/reperfusion (IR) arrhythmias via preserved calcium (Ca) cycling and mitochondrial function. We examined the protective effects of NR on regional IR in cultured neonatal rat ventricular myocyte monolayers. Optical mapping of intracellular Ca and mitochondrial membrane potential Δψm was performed using Rhod 2-AM and TMRE, respectively. Regional ischemia was mimicked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The coverslip IR model in the NRVM monolayer, originally developed by Pitts and Toombs [29], meets these criteria in several important ways: it creates a regional ischemic microenvironment that not only limits cellular access to oxygen and substrates, but also results in a restricted extracellular space, within which ischemic metabolites (e.g., lactate) and ions (H + , K + ) accumulate, just as in the ischemic heart. Moreover, the ability to simulate reperfusion and study the interface between the ischemic and non-ischemic cells in the monolayer allows one to examine the effects of heterogeneity in the excitable medium, essential for understanding the origin of arrhythmias, as demonstrated in previous optical mapping studies [30, 37]. An additional advantage realized in the present work is that the functional impact of IR at the macroscopic (whole monolayer) and microscopic (subcellular) level can be investigated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The coverslip IR model in the NRVM monolayer, originally developed by Pitts and Toombs [29], meets these criteria in several important ways: it creates a regional ischemic microenvironment that not only limits cellular access to oxygen and substrates, but also results in a restricted extracellular space, within which ischemic metabolites (e.g., lactate) and ions (H + , K + ) accumulate, just as in the ischemic heart. Moreover, the ability to simulate reperfusion and study the interface between the ischemic and non-ischemic cells in the monolayer allows one to examine the effects of heterogeneity in the excitable medium, essential for understanding the origin of arrhythmias, as demonstrated in previous optical mapping studies [30, 37]. An additional advantage realized in the present work is that the functional impact of IR at the macroscopic (whole monolayer) and microscopic (subcellular) level can be investigated.…”
Section: Discussionmentioning
confidence: 94%
“…Slow recovery of Cx43 phosphorylation was considered to be a major arrhythmogenic factor during early reperfusion. Later, Wang et al showed the protective effects of nutrition restriction preconditioning against IR using the same model [37]; post-ischemic mitochondrial depolarization was prevented and IR-induced arrhythmias were decreased, although the subcellular dynamics of ΔΨ m were not investigated. Our high resolution observations of the mitochondrial dynamics during IR, in the present work, strongly support the hypothesis that mitochondrial ΔΨ m instability plays a major role in post-ischemic arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Although S100A6 gene therapy provided a survival advantage after I/R, the challenge for translating this to clinical practice will be optimizing gene delivery for rapid transfection prior to or immediately after reperfusion. The exact mechanism behind this protective effect is unclear; however, we can speculate that the enhanced Ca 2+ cycling would attenuate diastolic Ca 2+ overload, thus suppressing arrhythmogenesis and leading to a reduction in reperfusion arrhythmias . All mortality occurred during occlusion or immediately on reperfusion, supporting an arrhythmic death.…”
Section: Discussionmentioning
confidence: 90%
“…The exact mechanism behind this protective effect is unclear; however, we can speculate that the enhanced Ca 2+ cycling would attenuate diastolic Ca 2+ overload, thus suppressing arrhythmogenesis and leading to a reduction in reperfusion arrhythmias. 32,33 All mortality occurred during occlusion or immediately on reperfusion, supporting an arrhythmic death.…”
Section: Discussionmentioning
confidence: 95%
“…Cola contains glucose/fructose, caffeine, water and some confidential components [29]. Long-term consumption of high sugar beverages may contribute to many diseases such as insulin resistance, obesity, hypertensive cardiovascular disease, and kidney disease [30]. However, there was no reported association of the cola with patients' health [31,32].…”
Section: Discussionmentioning
confidence: 99%